The use of case advocates to manage child survivors of sexual violence in public health facilities in Kenya: A qualitative study exploring the perceptions of child survivors, care givers and health care providers. (June 2021) - Digolo, Lina; Ajema, Carolyne; Kiruki, Millicent; Mireku, Maryline; Kotut, Ronald; Undie, Chi-Chi
Abstract: Background: The uptake of and retention in health services by child survivors of violence (CSV) is a growing challenge, especially in sub-Saharan Africa. While lay health workers have been used in several settings to improve access to health services, there is limited literature on the use of such workers to support services for CSV. Objective: To explore the acceptability of using trained lay health workers (case advocates) to provide basic information and escort CSV to various referral points within two public health facilities in Kenya. Participants: The following participants were enrolled after giving their consent: CSV 14–18 years of age presenting for services along with their caregivers during the study; caregivers above age 18; and healthcare providers (HCPs) providing services for sexual violence at the two study sites. Methods: In-depth interviews (14 with CSV and 27 with caregivers) and four focus group discussions (with 30 HCPs) were conducted. Data were transcribed in MSWord and analysed using a grounded theory analytical approach. Results: Caregivers and CSV reported that the case advocates were useful in fast-tracking access to services, easing CSV movement through health facilities and helping CSV communicate their issues. HCPs reported improved timeliness and completeness of services due to the involvement of the case advocates. Conclusion: The use of case advocates to support CSV is acceptable to children, caregivers and HCPs. Task-sharing between case advocates and HCPs has the potential to improve the uptake of the various services offered to CSV, especially in resource-limited settings.